Lesson Plans : The Institutional Demands of Becoming a Teacher - Everitt, Judson G. (Book collections on Project MUSE., 2018)
"In Lesson Plans, Judson G. Everitt takes readers into the everyday worlds of teacher training, and reveals the complexities and dilemmas teacher candidates confront as they learn how to perform a job that many people assume anybody can do. Using rich qualitative data, Everitt analyzes how people make sense of their prospective jobs as teachers, and how their introduction to this profession is shaped by the institutionalized rules and practices of higher education, K-12 education, and gender. Trained to constantly adapt to various contingencies that routinely arise in schools and classrooms, teacher candidates learn that they must continually try to reconcile the competing expectations of their jobs to meet students' needs in an era of accountability. Lesson Plans reveals how institutions shape the ways we produce teachers, and how new teachers make sense of the multiple and complicated demands they face in their efforts to educate students"--